YAP1 dependent activation of TRX2 is essential for the response of Saccharomyces cerevisiae to oxidative stress by hydroperoxides. - Kuge, S (1994)
The role of the YAP1 transcription factor in the response of Saccharomyces cerevisiae cells to a variety of conditions that induce oxidative stress has been investigated. Cells deficient in YAP1 were found to be hypersensitive to hydroperoxides and thioloxidants, whereas overexpression of YAP1 conferred hyper-resistance to the same conditions. These treatments resulted in an increase in YAP1-specific binding to DNA together with an increase in YAP1 dependent transcription. Our results indicate that this increase is not due to an increase in synthesis of YAP1 protein, but rather results from modification of pre-existing protein. Using a specific genetic screen, the TRX2 gene, one of two genes of S. cerevisiae that encode thioredoxin protein, was identified as being essential for YAP1 dependent resistance to hydroperoxides. Furthermore, efficient expression of TRX2 was dependent on YAP1 and enhanced under conditions of oxidative stress.